A educação para a cidadania global da UNESCO e seus nexos com a formação de professores de educação física no Pará - BASTOS, Robson dos Santos (Universidade Federal do Pará, 2019)
This study is part of the graduate program in education of the Federal University of Pará (UFPA), in the line of teacher training: Teaching Work, Educational theories and practices. In this research, we had as general objective to analyze the possible nexus between education for Global citizenship, formatted by Unesco, and the proposed training is established in Teaching political projects of physical education courses public universities in the State of Pará. It is a documentary study, inspired by the Marxian tradition as a method of analysis and theory of knowledge. As categories of analysis, we use the citizenship and education for Global citizenship, teacher training and physical education. Thus, in this study, we examine the concept of global citizenship, since your design in the classical liberalism, passing by your state of ressignification Social Welfare, up your Constitution by neoliberalism, when develops, based on the logic of globalization of the capitalist economy The study also revealed the assumptions adopted by Unesco that subsidize education for Global citizenship, as well as their strategies to assist policymakers, teachers and institutions in the development of this proposal on education and training of teachers In addition, we identify the relationships established between the Unesco recommendations for teacher training based on ECG and national curriculum guidelines for the training of the Graduate in physical education, in order to identify the possible nexus of common aspects the ECG with the Pedagogic political projects of the course of physical education from the the University of the State of Pará (CEDF/ UEPA) and the Faculty of physical education from the Federal University of Pará (FEF/UFPA). The result of the research allowed us to conclude that, among the documents investigated, the PPC that guides the teaching at the Faculty of Physical Education of the Federal University of Pará (UFPA) is the one that presents significant links with UNESCO recommendations for the development of Education for Global Citizenship; On the other hand, the PPP of the Physical Education Course of the State University of Pará (UEPA) is in the opposite direction of a neoliberal proposal.